Defending the “Natural Family” in Lithuania: Gendered Nationalism and Familism in the Discourse of Right-Wing Populists - Juchnevičiūtė, Evelina (Sociologija. Mintis ir veiksmas, 2024)
The aim of this article is to examine the interplay between gender and nationalism in the political discourse of right-wing populists in Lithuania. In recent years, the political landscape in Central and Eastern Europe has been increasingly characterized by the rise of right-wing populism and anti-gender campaigns. The founding of the Lithuanian political party the National Alliance is linked to this shift. This party is defined as nationalist, conservative, anti-system and populist political movement. Employing political discourse analysis, this study analyses the National Alliance’ public statements from 2020 to 2024. The analysis shows that the discourse of the National Alliance uses a hyperbolic and alarmist language to represent progressive gender policies, invokes gendered nationalist and familist notions to delegitimize them, and advocates a model of society based around the “natural family” in which identity is controlled and space for expressions of non-conformity is restricted.